The Influence of Sharing Fake News, Self-regulation, Cyber Bullying on Social Media Fatigue during COVID-19 Depression as Mediator Role - Khawaja, Wasim Shahid; Raza, Muhammad; Israr, Aqeel; Aziz, Atif; Shaikh, Ubedullah Amjad Ali (Pakistan Journal of Humanities and Social Sciences, 2023)
Intent of this is to explore the empirical impact of fake news sharing, self-regulation and cyberbullying while depression been playing a role of the mediator on the fatigue of social media in the pandemic, COVID- 19. In order to bridge the gap in the current study, a conceptual framework has been utilized to find out the impact of fatigue of social media on depression. SMART PLS software has been used in this study to investigate the influence of the fake news, self-regulation and cyberbullying on the social media with variable depression as a mediator. Model has been tested on the sample size of 132. Also, research design of the current study is cross sectional. the foundation of this study is based on the (CLT) cognitive load theory which gave insight on effects of social media on the minds of the individuals. A report claimed that Facebook has broke its own records of usage during the pandemic. The existing study has also explored every possible mechanism of fake news countering that is being created by the Facebook pages of the real and actual newscast. However, it also uses the advertisement for disseminating the real, actual or correct information. This research will also be developing the great and more understanding among the effect of SMA, self-regulation, and cyberbullying with the impact of depression as a mediator on the fatigue of social media in pandemic times. For Karachi respondents, a close ended questionnaire has been designed in order to test the research models. Respondents were social media’s adolescent users in Karachi, Pakistan. Untruth news sharing, cyberbullying, and self- regulation has indirectly projected the social media fatigue in the presence of depression as a mediator. Moreover, due to the current study limitations, it is suggested to conduct more studies in the future on the same variables in different regions.